2015
DOI: 10.2527/jas.2015-9081
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of short-chain fatty acids and energy production from hindgut fermentation in cannulated pigs fed graded levels of wheat bran1

Abstract: This study investigated the amount of energy available to growing pigs from fermentation of dietary fiber in the hindgut. Eighteen growing barrows, fitted with a simple T-shaped cannula at the terminal ileum, were allocated to 3 experimental diets in a completely randomized design. The 3 diets were a standard-fiber diet (SFD), which contained 75.1 g NDF/kg diet; a medium-fiber diet (MFD) of 105.7 g NDF/kg diet; and a high-fiber diet (HFD), which contained 146.9 g NDF/kg diet. Each diet had 6 replicate pigs. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
1
23
1
Order By: Relevance
“…However, Asian/African diets have higher fibre content, which may indicate a higher energy contribution from fibre fermentation to the host. This was corroborated in a study in pigs, which have similar intestinal functions to humans, showing that an increase in dietary fibre from 75 to 147 g kg −1 increased energy contribution from 10.7% to 24.2% . Thus, a slight increase in microbial fermentation (1%) could provide 20 kcal day −1 extra energy based on a diet of 2000 kcal day −1 , resulting in 1 kg of weight gain per year .…”
Section: The Gut Microbiota As An Environmental Factor Contributes Tomentioning
confidence: 97%
“…However, Asian/African diets have higher fibre content, which may indicate a higher energy contribution from fibre fermentation to the host. This was corroborated in a study in pigs, which have similar intestinal functions to humans, showing that an increase in dietary fibre from 75 to 147 g kg −1 increased energy contribution from 10.7% to 24.2% . Thus, a slight increase in microbial fermentation (1%) could provide 20 kcal day −1 extra energy based on a diet of 2000 kcal day −1 , resulting in 1 kg of weight gain per year .…”
Section: The Gut Microbiota As An Environmental Factor Contributes Tomentioning
confidence: 97%
“…The design of 6 open-circuit respiration chambers were reported by van Milgen et al [13] and Lyu et al [11]. Volume of each chamber was approximately 7.8 m 3 , and relative humidity in chamber was controlled at 70%. During the feeding period, the temperature was 22°C, and it was increased to 24°C on the fasted day.…”
Section: Animals and Experimental Proceduresmentioning
confidence: 99%
“…Major end products from these fermentations are the short-chain fatty acids (SCFA) [2], mainly acetate, propionate, and butyrate. Recent studies show that SCFA from microbial fermentation generates 11% to 24% of the total digestible energy (DE) as wheat bran (WB) level increases from 10% to 30% when fed to pigs [3]. It suggests that DF has a final impact on energy metabolism by shaping microbes and regulating SCFA production [4].…”
Section: Introductionmentioning
confidence: 99%
“…Contribution of available energy from hindgut fermentation (%) = (energy absorbed from hindgut VFA (kcal/kg DM feed) / (energy digested in the ileum (kcal/kg DM feed) + energy absorbed from hindgut VFA(kcal/kg DM feed))) × 100 (Iyayi and Adeola, 2015).…”
Section: ( )mentioning
confidence: 99%
“…Previous studies have indicated that nutrient utilization and performance is depressed when pigs are fed nutritionally-balanced high-fiber diets that contain added fat (Bakker, 1996;Gutiérrez et al, 2013). An increase in DF cause a reduction in digestible energy of pig diets (Bach Knudsen and Hansen, 1991) and promotes hindgut VFA production and absorption (Iyayi and Adeola, 2015;Montoya et al, 2016). Different fiber sources are fermented at different rates and the solubility of DF is important in determining fermentability of DF and the quantity of VFA produced (Bach Knudsen, 2001;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%